Comparison of 2 and 4 Intratympanic Steroid Injections in the Treatment of Idiopathic Sudden Sensorineural Hearing Loss. (April 2018) - Suzuki, Hideaki; Wakasugi, Tetsuro; Kitamura, Takuro; Koizumi, Hiroki; Do, Ba Hung; Ohbuchi, Toyoaki
Objective: We studied the effect of intratympanic steroid administration with different total injection times on hearing outcomes in patients with idiopathic sudden sensorineural hearing loss (ISSNHL). Methods: The subjects were 191 consecutive patients (192 ears) with ISSNHL (hearing level ≥40 dB, interval between onset and treatment ≤30 days). They received systemic prednisolone (100 mg followed by tapered doses) combined with intratympanic injection of dexamethasone (4 mg/ml). Intratympanic injection was performed 4 times (days 1, 2, 4, and 7) in 92 patients (92 ears) or 2 times (days 1 and 2) in 99 patients (100 ears). The hearing outcomes were evaluated at 1 week from the start of treatment and 1 to 2 months after the completion of treatment. Results: There was no significant difference in hearing outcomes between the 4- and 2-injection groups at either time point. Multiple regression analysis also showed that the hearing level after treatment did not depend on the total number of intratympanic steroid injections. Conclusion: These results indicate that a protocol using only 2 intratympanic steroid injections exerts a sufficient effect on the hearing outcomes of ISSNHL. This simplified treatment protocol would be greatly beneficial to relieve the physical and mental stress of patients.